Effect of Mulching Materials and Spacing on Growth and Yield of Two Varieties of Chilli Pepper (Capsicum annum L.) Planted in Experimental Plot in Jericho area of Ibadan Northwest Local Government, Oyo State, Nigeria - O. A. Adesida; T. O. Bamigboye; A. M. Aderemi; A. O. Akala; O. A. Ogidan (Journal of Applied Sciences and Environmental Management, 2024)
Mulching is covering the soil surface around the plants with organic or synthetic material to create favorable conditions for plant growth and proficient crop production. Hence, the objective of this paper is to investigate the Effect of Mulching Materials and Spacing on Growth and Yield of Two Varieties of Chilli Pepper (Capsicum annum L.) Planted in Experimental Plot in Jericho area of Ibadan Northwest Local Government, Oyo State, Nigeria using appropriate standard techniques. The results obtained from the experiment showed no significant difference in the growth parameters of both varieties except in the fruit yield data of the local variety assessed. Treatments which recorded highest values for hybrid and local variety on plant height, stem diameter, number of leaves, number of flowers and number of fruits were T2(27.7cm), T2(1.2mm), T2(64.0),  T2(5.00) and T2(17.0) while treatments which recorded least were T4(20.3cm), T4(0.7mm),T5( 20), T4 ( 1.00)  T3 (0.00) respectively. In conclusion, T1 (30x75cm+plantain leaves), hybrid variety recorded the best performance while for local variety, T2 (60cmx75cm+plantain leaves) recorded highest than other treatments assessed. It was therefore recommended that spacing of 30cmx75cm and plantain leaves should be adopted for the growth and yield of Capsicum annum hybrid varieties while 60x75cm and plantain leaves can be used for local varieties in the study area.